A constant N2H+ (1-0)-to-HCN (1-0) ratio on kiloparsec scales - Jiménez-Donaire, Maria Jesús; Usero, A.; Bešlić, I.; Tafalla, M.; Chacón-Tanarro, A.; Salomé, Q.; Eibensteiner, C.; García-Rodríguez, A.; Hacar, A.; Barnes, A. T.; Bigiel, Frank; Chevance, Mélanie; et al. (Astronomy and astrophysics, 2023)
Nitrogen hydrides such as NH3 and N2H+ are widely used by Galactic observers to trace the cold dense regions of the interstellar medium. In external galaxies, because of limited sensitivity, HCN has become the most common tracer of dense gas over large parts of galaxies. We provide the first systematic measurements of N2H+ (1-0) across different environments of an external spiral galaxy, NGC 6946. We find a strong correlation (r > 0.98, p < 0.01) between the HCN (1-0) and N2H+ (1-0) intensities across the inner ∼8 kpc of the galaxy, at kiloparsec scales. ...
Gesehen am 29.11.2023